2012
DOI: 10.1016/j.jmmm.2012.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Exchange bias of mu-metal thin films

Abstract: The exchange bias of the soft ferromagnet mu-metal, Ni 77 Fe 14 Cu 5 Mo 4 , with the metallic antiferromagnet Fe 50 Mn 50 has been studied as a function of ferromagnet thickness and buffer layer material. Mu-metal exhibits classic exchange bias behavior: the exchange bias (H EB ) and coercive fields scale inversely with the ferromagnet's thickness, with H EB varying as the cosine of the in-plane applied field angle. While the exchange bias, coercivity, and exchange energy are greatest when the buffer layer mat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…8-12 X-ray diffraction measurements performed using Bruker-AXS Discover D8 diffractometer show overlap of (111) peak for all layers similarly to the results presented in Ref. 13.…”
supporting
confidence: 61%
“…8-12 X-ray diffraction measurements performed using Bruker-AXS Discover D8 diffractometer show overlap of (111) peak for all layers similarly to the results presented in Ref. 13.…”
supporting
confidence: 61%
“…In 1956, Meiklejion et al found exchange bias by studying Co particle shrouded by CoO. Ever since, people have found exchange bias at FM-AFM /Ferri-FM/Ferri-AFM interfaces [1][2][3][4][5][6]. Exchange bias exists in mono-crystal and poly-crystal samples and thin film samples [7][8][9][10][11][12][13][14][15], suggesting that exchange bias is an internal trait of these systems, but not related to synthesis methods.…”
Section: Introductionmentioning
confidence: 99%